Why we hate - Levin, Jack (Prometheus Books, 2004)
In the aftermath of 9/11 -- Hate as violence -- Hate as fear -- Hate as revenge -- Hate and human nature -- The political uses of hate -- Hate and culture wars -- Hate in popular culture -- When the economy goes South, hate travels North -- Manufacturing hate -- Ordinary people; extraordinary courage -- Cooperation and community action -- Women as peacemakers -- Societies that resist hate and violence -- Ending hate and violence -- The modern madness of hate: an epilogue.